2020
DOI: 10.2147/opth.s242422
|View full text |Cite
|
Sign up to set email alerts
|

<p>Tear Film Characteristics During Wear of Daily Disposable Contact Lenses</p>

Abstract: To evaluate changes induced over time by three daily disposable (DD) contact lenses on tear meniscus height (TMH), pre-lens non-invasive break-up time (pre-lens NIBUT), tear film osmolarity (TO) and objective quality of vision (OQV). Patients and Methods: Forty-six subjects enrolled in this prospective open-label unmasked non-randomized simultaneous comparative cross-over study. For the first week of the study, subjects wore a nesofilcon A lens in the right eye and a delefilcon A lens in the left eye. After 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Nesofilcon A is a new generation hydrogel DDCL that has a surface wetting technology with a polymer-bound macromer for maintaining a higher water content 78%. 12 A stable average NIBUT score with 8 h of wearing was previously reported in both presbyopic and non-presbyopic wearers. 19 However, the nesofilcon A group showed the lowest scores from the beginning of 4 h to 12 h compared to the other two SiHy DDCL groups.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Nesofilcon A is a new generation hydrogel DDCL that has a surface wetting technology with a polymer-bound macromer for maintaining a higher water content 78%. 12 A stable average NIBUT score with 8 h of wearing was previously reported in both presbyopic and non-presbyopic wearers. 19 However, the nesofilcon A group showed the lowest scores from the beginning of 4 h to 12 h compared to the other two SiHy DDCL groups.…”
Section: Discussionmentioning
confidence: 67%
“…11 Nesofilcon A (Biotrue ONEday™, Bausch & Lomb, Rochester, New York, USA) is a widely used, high-quality, and well-accepted conventional hydrogel (Hy) DDCL material with 78% water content throughout and a surface that retains water, like the natural tear film of the polymer-bound surface active macromer poloxamer 407. 12 To identify the most appropriate DDCL material in terms of tear film stabilization, ocular comfort levels, and visual quality for prolonged use, we compared the novel SiHy DDCL of Verofilcon A with another SiHy DDCL of Senofilcon A and a Hy DDCL of nesofilcon A.…”
Section: Introductionmentioning
confidence: 99%
“…Although break-up areas cannot be visualized with fluorescein dye during SCL wear, non-invasive tear break-up analysis using concentric ring patterns confirms that the PrLTF exhibits tear break up [38,40]. Therefore, localized evaporation-driven osmolarity spikes in the PrLTF are anticipated to be similar to those on the pre-corneal tear film during no-lens wear.…”
Section: Methodsmentioning
confidence: 95%
“…Previous studies have confirmed that 3–5 min adaption is enough for accommodation [ 29 , 30 , 31 ]. Montani [ 32 ] also found that tear film was unchanged at 20 min wear of all lenses but was significantly reduced after 8 h. Hence, the 20 min rest is more than sufficient for accommodation and tear-film adaption. Sanders and McCormick pointed out that when reading a book or paper-like material, the normal reading distance is usually somewhere between 305 and 406 mm, with a mean of 355 mm.…”
Section: Methodsmentioning
confidence: 99%